Options for methane mitigation in China's rice sector - Yang, Jintao; Zhang, Yumei; Zhang, Ruizeng; Fan, Shenggen; Zhou, Sheng; Li, Yangyang; Wang, Bin; Yang, Xiaoguang; Chen, Kevin Z. (China Agricultural University, 2025)
The world’s freshwater systems are buckling under pressure from climate change, pollution and over-extraction. Water demand is predicted to exceed supply by 40% within five years. Agriculture – which consumes 70% of freshwater withdrawals – is at particular risk, given food production must increase 60% by mid-century. The food-water nexus is now a critical imperative: humanity needs to rebalance its relationship with water.